Re-Engagement in Physical Activity Slows the Decline in Older Adults’ Well-Being – A Longitudinal Study - Hon Lon Tam PhD; Kai Chow Choi PhD; Ying Lau PhD; Leona Yuen Ling Leung DN; Alex Siu Wing Chan PhD; Lilin Zhou BSc; Eliza Mi Ling Wong PhD; Jonathan Ka Ming Ho DN (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Physical activity is recommended for older adults; however, the benefits of previous active engagement in physical activity that can be sustained after one becomes inactive remain to be determined. This study investigated the longitudinal associations between physical activity engagement patterns and older adults’ well-being. This population-based cohort study used data from the China Health and Retirement Longitudinal Study between 2015 and 2020. People aged 60 years and above were included, and they were categorized as active engagers if they reported engaging in at least 10 min of moderate and/or vigorous exercise consecutively per week in each survey year. Older adults’ well-being was evaluated using the healthy aging score, and geographical variations were visualized. The generalized estimating equations model was adopted to examine the differences between various physical activity engagement patterns and older adults’ well-being. Among the 3300 older adults (50.5% men; age 66.9 ± 5.7 years) during the five years of follow-up, engagement in physical activity increased from 31.7% to 59.6%. However, their well-being decreased gradually, especially among those who were inactive engagers (beta = −0.20 to −0.21). Physical activity engagement patterns appeared to slow decline in well-being. Geographical variations were noted, with more favorable healthy aging scores observed in northern China than in southern China. As older adults age, well-being deteriorates, and disengagement of physical activity accelerates the rate of decline. Re-engagement in physical activity can slow the rate of decline in well-being. Early identification of and intervention in inactive engagement in physical activity reduce the detrimental effects on older adult’s well-being. A national health initiative is an effective strategy to create a supportive environment for older adults to continue and engage in physical activity. The participation of healthcare professionals and community parties is important to encourage and engage older adults in physical activity.